Self-cementing properties of recycled concrete aggregates (RCA) on the example of tests of material and layers of pavement subbase - Fengier, Jakub; Pożarycki, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The work is an attempt to summarize the experience concerning the diagnosis of the practical properties of recycled aggregate concrete cement (RCA). It describes the phenomenon of self-cementing properties which was investigated in both the laboratory and on field tests including compressive strength of RCA, non-conventional oedometric tests of RCA and plate bearing tests on the surface of RCA layer. The described self-cementing properties were remarked, however, the RCA material was characterized by smaller increase in the value of parameter EV2 in a 2-year period of time than recycled concrete materials described in the available literature.